2003
DOI: 10.1046/j.1440-1746.2003.03014.x
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of calprotectin in gastroenterology

Abstract: Calprotectin is a calcium and zinc binding protein of the S100 family derived predominantly from neutrophils and monocytes. It is detectable in body fluids and tissue samples and is emerging as a valuable marker in the diagnosis, and the monitoring and determining of the prognosis of commonly encountered gastroenterological conditions. Fecal calprotectin, in particular, has for a long time been regarded as a promising marker of gastrointestinal pathology and has now been established as a routine test in Norway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 60 publications
4
80
0
1
Order By: Relevance
“…However, fecal calprotectin can only refl ect the excretion of neutrophils. Many infective diseases can cause a large number of neutrophils to infiltrate, so that fecal calprotectin is elevated in a number of organic gastroenterological disorders [29][30][31] . Therefore, fecal calprotectin is not desirable as a method that is required to differentiate efficiently between UC and infective colitis, so it cannot take the place of an endoscope in diagnosing UC.…”
Section: Discussionmentioning
confidence: 99%
“…However, fecal calprotectin can only refl ect the excretion of neutrophils. Many infective diseases can cause a large number of neutrophils to infiltrate, so that fecal calprotectin is elevated in a number of organic gastroenterological disorders [29][30][31] . Therefore, fecal calprotectin is not desirable as a method that is required to differentiate efficiently between UC and infective colitis, so it cannot take the place of an endoscope in diagnosing UC.…”
Section: Discussionmentioning
confidence: 99%
“…S100A8 was another biomarker identified in the Apc Minϩ/Ϫ mouse adenomas, and we further confirmed that its expression increases as human CRC progresses from normal to higher stages (Duke's stages A-D) at both the protein and RNA levels in two relatively large human CRC sample sets. S100A8 binds with calgranulin B to form a complex called calprotectin (43). As a calcium-and zinc-binding protein, calprotectin is a multipotent molecule and can inhibit several zinc-dependent metalloproteinases by sequestration of zinc (44).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased levels of fecal calprotectin have been reported in patients with several other inflammatory conditions of the lower gastrointestinal tract and even in patients affected by neoplastic disease of both upper and lower gastrointestinal tract (Brydon et al, 2001;Poullis et al, 2003). Therefore, measuring fecal calprotectin has been proposed as useful noninvasive diagnostic tool for differentiating patients with organic disease of the intestinal tract from those with functional diseases.…”
Section: Introductionmentioning
confidence: 99%